Has the Basel Accord Improved Risk Management During the Global Financial Crisis? - Michael McAleer; Juan-Ángel Jiménez-Martín; Teodosio Pérez-Amaral (Tinbergen Institute, 2013)
The Basel II Accord requires that banks and other Authorized Deposit-taking Institutions (ADIs) communicate their daily risk forecasts to the appropriate monetary authorities at the beginning of each trading day, using one or more risk models to measure Value-at-Risk (VaR). The risk estimates of these models are used to determine capital requirements and associated capital costs of ADIs, depending in part on the number of previous violations, whereby realised losses exceed the estimated VaR. In this paper we define risk management in terms of choosing from a variety of risk models, and discuss the selection of optimal risk models. A new approach to model selection for predicting VaR is proposed, consisting of combining alternative risk models, and we compare conservative and aggressive strategies for choosing between VaR models. We then examine how different risk management strategies performed during the 2008-09 global financial crisis. These issues are illustrated using Standard and Poor's 500 Composite Index.
urn:NBN:nl:ui:15-1765/38233
Keywords: G32; G11; G17; C53; C22; 330; Value-at-Risk (VaR); daily capital charges; violation penalties; optimizing strategy; risk forecasts; aggressive or conservative risk management strategies; Basel Accord; global financial crisis; Basler Akkord; Einlagengeschäft; Risikomaß; Unternehmenspublizität; Finanzkrise; Welt